Plication of the free wall of the left ventricle in dogs with doxorubicin-induced cardiomyopathy - de Andrade, James N.B.M. [UNESP]; Camacho, Aparecido A. [UNESP]; Santos, Paulo S.P. [UNESP]; Fantinatti, Alexandra P. [UNESP]; Nunes, Newton [UNESP]; Stopiglia, Angelo J. (American Veterinary Medical Association (AVMA), 2005)
Objective - To evaluate plication of the free wall of the left ventricle, which reduces the left ventricular area and volume, as a method to improve the left ventricular systolic function without cardiopulmonary bypass. Animals - 8 mixed-breed adult dogs. Procedure - Dilated cardiomyopathy (DCM) was induced in each dog by administration of doxorubicin (30 mg/m2, IV, q 21 d for 168 days). Two dogs died during induction of cardiomyopathy. Plication surgery was performed in 4 dogs. Two dogs did not ondergo to surgery (control group). Values for cardiac output (CO), 2-dimensional and M-mode echocardiography, arterial blood pressure, electrocardiography, blood cell counts, and serum biochemical analyses were recorded after induction of DCM (baseline) and 1, 2, 7, 15, 21, 30, 60, 90, 120, 150, and 180 days after plication surgery. Ambulatory ECG (Holter) recordings were conducted for 24 hours on the day of surgery. Results - 1 dog died after plication surgery. The remaining dogs undergoing ventricular plication had a significant improvement in CO, ejection fraction, and fractional shortening and reductions of left ventricular area and volume after surgery. Electrocardiographic and Holter recordings revealed premature ventricular complexes, which resolved without treatment during the first week after surgery. Clinical condition of the control dogs declined, and these 2 dogs died approximately 40 days after induction of cardiomyopathy. Conclusions and Clinical Relevance - Plication of the free wall of the left ventricle improved left ventricular systolic function in dogs with doxorubicin-induced cardiomyopathy. Additional studies are needed to evaluate its application in dogs with naturally developing DCM.
Keywords: doxorubicin; animal experiment; animal model; arterial pressure; blood analysis; blood cell count; blood vessel wall; cardiopulmonary bypass; congestive cardiomyopathy; controlled study; death; dog disease; drug induced disease; heart ejection fraction; heart left ventricle; heart left ventricle function; heart left ventricle volume; heart output; heart surgery; Holter monitoring; M mode echocardiography; nonhuman; surgical technique; treatment outcome; two dimensional echocardiography; Animals; Antibiotics, Antineoplastic; Cardiac Output; Cardiomyopathy, Dilated; Disease Models, Animal; Dog Diseases; Dogs; Doxorubicin; Echocardiography; Stroke Volume; Systole; Ventricular Remodeling; Animalia; Canis familiaris